Persepsi Pelaku Usaha Marine product di Desa Lontar Kabupaten Serang Provinsi Banten Terhadap Layanan Sertifikasi Halal - Siti Widiati; Lana Izzul Azkia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Lontar Village has the potential for mangrove forests, which could be used as a local economic resource. This needs to be developed because it is currently operated on a household basis and is still limited by marketing access. Halal certification is one way to create local business products. The aim of this research is to analyze business actors' perceptions of halal certification services for Marine products in Lontar Village and formulate a priority development strategy. Qualitative descriptive methods and SWOT analysis are used in this study. According to the research, Lontar Village's business community is well aware of the value of halal certification and how it can increase market share and product quality. Using marine resources, enhancing market systems, strengthening infrastructure, creating new products, applying climate change risk management, and halal certification are the main growth strategies.